PENGELOLAAN PIUTANG YANG EFEKTIF DALAM UPAYA MENINGKATKAN RENTABILITAS DAN MENJAGA LIKUIDITAS (Studi Kasus pada Unit Simpan Pinjam KUD Tani Wilis Kec Sendang Kab Tulungagung Periode 2012-2014) - Rizka Milatul Husna (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
An efficient Account receivable management required to achieve the planned objectives. The efficiency of the company can be seen from the level of profitability and liquidity. This research is purpose to determine the efficient account receivable management in order to improve profitability and maintain liquidity. The method used is descriptive research method with a case study approach. Data analysis was to determine the policy of credit and account receivables management, calculating financial ratios, make a cash budget and projection of financial statements in 2015, which was then compared by financial ratios data analysis of 2014 and 2015. Results of this study is Unit simpan pinjam KUD Tani Wiliss less efficient in managing their receivables can be seen from the level of profitability and liquidity fluctuates every year